Biosynthesis and Characterization of Zinc Oxide Nanoparticles and Their Impact on the Composition of Gut Microbiota in Healthy and Attention-Deficit Hyperactivity Disorder Children - Zhou, Guoling; Yu, Rongrong; Ahmed, Temoor; Jiang, Hubiao; Zhang, Muchen; Lv, Luqiong; Alhumaydhi, Fahad A.; Allemailem, Khaled S.; Li, Bin (Frontiers in Microbiology, 2021)
Attention deficit hyperactivity disorder (ADHD) seriously affects children's health, while the gut microbiome has been widely hypothesized to play a role in the regulation of ADHD behavior. The present study aims to the biosynthesis of zinc nanoparticles (ZnONPs) by using Acinetobacter johnsonii strain RTN1, followed by their characterization through state of the art material characterization techniques viz., UV–vis spectroscopy, FTIR, SEM-EDS, and TEM analysis. Moreover, we investigated and compared the population composition of gut microbiota and their susceptibility to biogenic ZnONPs between healthy and ADHD children based on the traditional plate method and 16S rRNA amplicon sequence analysis. The antibacterial effect of ZnONPs against gut bacteria was also determined by measurement of live cell number, living/dead bacterial staining test and flow cytometry observation. The present study revealed that the number of live gut bacteria in healthy children was more than 10-fold higher than that in ADHD children, however, the community structure of gut bacteria has changed, while greater diversity was found in gut bacteria from ADHD children. In addition, we found that the number of live gut bacteria in healthy and ADHD children was reduced by ZnONPs, which shows an increased and reduced effect in composition of gut bacteria from healthy and ADHD children, respectively. It was also noted that the main mechanism of ZnONPs may be to inhibit the growth of gut bacteria rather than to kill them, while the nanoparticle-resistant strains in healthy children is also different from that in ADHD children. Some representative bacteria in particular nanoparticle-resistant bacteria were successfully isolated and identified. Overall, this study revealed the importance of gut bacteria in development of ADHD and provided a new possibility to prevent ADHD by the combination nanoparticle and its resistant bacteria.